Classification of Aristolochia species based on GC-MS and chemometric analyses of essential oils - Francisco, Carla S. [UNESP]; Messiano, Gisele B. [UNESP]; Lopes, Lucia Maria Xavier [UNESP]; Tininis, Aristeu G. [UNESP]; de Oliveira, Jos E. [UNESP]; Capellari, Lindolpho (Pergamon-Elsevier B.V. Ltd, 2008)
Essential oils were obtained from roots of 10 Aristolochia species by hydrodistillation and analysed by GC MS. A total of 75 compounds were identified in the analysed oils. Multivariate analyses of the chemical constituents of the roots enabled classification of the species into four morphological groups. These forms of analysis represent an aid in identification of further specimens belonging to these species. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Aristolochia; Aristolochiaceae; essential oils; multivariate analysis; principal component analysis; morphology; monoterpene; sesquiterpene